A novel Threat Evaluation method for privacy-aware system in RFID. (11th November 2011) - Tian, Yuan; Song, Biao; Huh, Eui-Nam
Radio Frequency Identification (RFID) is used in an increasing number of commercial and scientific applications. The lack of a unified RFID standard and the diversity of available technologies make it difficult to safeguard privacy without being to identify potential threats in advance. To address this problem, we present a threat evaluation system intended to enhance privacy in RFID. Our proposed model allows users to customise services based on their evaluations of potential threats. Furthermore, prospective users may refer to previous user feedback to evaluate the reliability of different service providers and to aid in the selection of suitable commercially-available services.